2016
DOI: 10.1038/srep37836
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Hypermethylation of the VDAC2 Promoter is a Potential Cause of Idiopathic Asthenospermia in Men

Abstract: This study aimed to explore the association between the methylation status of the VDAC2 gene promoter region and idiopathic asthenospermia (IAS). Twenty-five IAS patients and 27 fertile normozoospermia (NZ) were involved. GC-2spd cells were treated with different concentrations of 5-aza-2′-deoxycytidine (5-Aza-CdR) for 24 h and 48 h. qRT-PCR was conducted to reveal whether or not VDAC2 expression was regulated by methylated modification. A dual-luciferase activity detection was used to verify VDAC2 promoter ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This protein has a critical role in the transportation of ions and small molecules in spermatozoa through the lipid bilayer 42,43 . Several studies demonstrated that abnormal activity and alteration of this protein concentration have inimical effects on sperm function and fertility via alteration of ionic influx 4446 . Since freezing/thawing step is associated with increased osmotic stress mediated via ionic imbalance, thus VDAC2 can be a candidate marker for predicting sperm freezability.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has a critical role in the transportation of ions and small molecules in spermatozoa through the lipid bilayer 42,43 . Several studies demonstrated that abnormal activity and alteration of this protein concentration have inimical effects on sperm function and fertility via alteration of ionic influx 4446 . Since freezing/thawing step is associated with increased osmotic stress mediated via ionic imbalance, thus VDAC2 can be a candidate marker for predicting sperm freezability.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of VDAC2 promoter in a mammal’s developing ovary triggered by GATA1 and Cellular and viral myb-like transcriptional regulators (MYBL2) transcription factors lead to autophagy inhibition confirming its relevant role in cell survival [ 29 ]. In human male abnormal hypermethylation of VDAC2 promoter correlated with idiopathic asthenospermia while in complete unmethylation or mild hypermethylation, sperm motility improved confirming the role of VDAC2 expression in human spermatozoa [ 30 ]. The increased expression level of the VDAC1 transcript was also induced by a lncRNA through enhancement of H3K4me3 levels in its promoter, leading to apoptosis of placental trophoblast cells during early recurrent miscarriage [ 31 ].…”
Section: Introductionmentioning
confidence: 98%
“…The hypermethylation at the promoter region of the MTHFR has shown to down regulate the MTHFR expression, and as a result its enzymatic activity is reduced, leading to non-obstructive azoospermia (NOA) and potentially idiopathic infertility [ 57 59 ]. Likewise, hypermethylation of VDAC2 promoter region might reduce sperm motility, ultimately result in idiopathic asthenospermia [ 60 ]. In the regions of regulatory promoters, which are associated with the silencing of tumour suppressor genes, the hypermethylation can lead to testicular germ cell tumours [ 61 ].…”
Section: Alteration Of Epigenetic Modifications and Corresponding Dismentioning
confidence: 99%